World History: Ancient History, United States History, European, Native American, Russian, Chinese, African, Asian, Indian and Australian History, Wars including World War1 and 2 - Brown, Adam ([Place of publication not identified] : [Adam Brown], 2016)
"This book contains the history of the entire world, as we know it."
Keywords: World history; English language